Effectiveness of Health Education-oriented Program on Parents’ Awareness towards Adolescents’ Violence Control in Baghdad City - Sajem, Kareem; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2010)
Objective: This study aims to determine the effectiveness of health education oriented program on parents’ awareness towards adolescents’ violence control. Methodology: A quasi-experimental study was carried out in Baghdad city form 1st of April, 2008 to 1st of September, 2009. A purposive "non-probability" sample of 60 parents who have adolescents’ violence in their families who were selected according to specific criteria. The researcher divided the samples into two equal groups; the study and control groups. The health education program, as well as a questionnaire was constructed as tools for data collection by the researcher for the purpose of the study. Content validity was determined by a panel of experts in different specialties. Reliability of instrument was determined by the use of test-retest approach through the pilot study which was carried out from October, 1 st , 2008 to October, 22nd , 2008. Data were analyzed through the application of the descriptive statistics (frequency, percentage and mean), and inferential statistics (person correlation coefficient and t-test). Results: Results of the study indicates that there is a significant comparative difference between parents’ awareness towards adolescents’ violence control in the study and control groups through the pre-test, post-test-Ι and post-test-ΙΙ. (after 3 to 4 weeks of post-test, for these results program is successful and can be considered as an effective means to increase parents’ awareness. Recommendations: The study recommended that such program can be implemented in form of sessions for parents of adolescents in schools or reformation of juveniles to increase their awareness.